Post-translational modifications of collagen and its related diseases in metabolic pathways - Linghong Guo; Weiyi Xiang; Zhaoping Pan; He Gu; Xian Jiang (Acta Pharmaceutica Sinica B)
As the most abundant and essential structural protein in the human body, collagen is ubiquitously present in the interstitium of nearly all solid organs, playing a crucial role in maintaining the structural integrity and functional stability of human tissues and organs. Disorders associated with collagen structure and metabolisms impose a significant burden on society and healthcare systems. Post-translational modifications (PTMs) are essential steps in collagen metabolism, and recent studies have indicated that aberrant regulation of PTMs plays a pivotal role in the pathogenesis and progress of collagen-related disorders, including liver, kidney, heart, lung, and skin fibrosis, as well as keloid. This review provides a comprehensive summary of the regulatory mechanisms of both traditional and novel PTMs in collagen metabolism and collagen-related diseases. Furthermore, we summarize the drugs that modulate PTMs and their effects, with the aim of elucidating the pathophysiology of collagen-related diseases and provide new insights for their diagnosis, prevention, and treatment.